2016
DOI: 10.1556/1886.2016.00026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RpoN, RpoS and LuxS pathways on the biofilm formation and antibiotIc sensitivity of Borrelia burgdorferi

Abstract: Borrelia burgdorferi, the causative agent of Lyme disease, is capable of forming biofilm in vivo and in vitro, a structure well known for its resistance to antimicrobial agents. For the formation of biofilm, signaling processes are required to communicate with the surrounding environment such as it was shown for the RpoN–RpoS alternative sigma factor and for the LuxS quorum-sensing pathways. Therefore, in this study, the wild-type B. burgdorferi and different mutant strains lacking RpoN, RpoS, and LuxS genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 65 publications
(75 reference statements)
1
22
0
Order By: Relevance
“…Moreover, drug responses of stationary phase ∆rel Bbu Bb have not yet been tested, so it remains unclear whether the relationship between the stringent response and Borrelia antibiotic tolerance is causal or correlational. Meanwhile, there is some indication that eliminating LuxS, the enzyme responsible for biosynthesis of the quorum sensing autoinducer, impacts both borrelial viability and aggregate structures of stationary phase cultures treated with sub-MBC concentrations of doxycycline [271]. Ultimately, clarity is required around the contributions of these and other environmental response networks to Borrelia pathophysiology and persistence.…”
Section: Borrelial Antibiotic Persistencementioning
confidence: 99%
“…Moreover, drug responses of stationary phase ∆rel Bbu Bb have not yet been tested, so it remains unclear whether the relationship between the stringent response and Borrelia antibiotic tolerance is causal or correlational. Meanwhile, there is some indication that eliminating LuxS, the enzyme responsible for biosynthesis of the quorum sensing autoinducer, impacts both borrelial viability and aggregate structures of stationary phase cultures treated with sub-MBC concentrations of doxycycline [271]. Ultimately, clarity is required around the contributions of these and other environmental response networks to Borrelia pathophysiology and persistence.…”
Section: Borrelial Antibiotic Persistencementioning
confidence: 99%
“…In the past several years, a novel aggregate form, called biofilm, was found for Borrelia and was shown to be very antimicrobial resistant vitro and in vivo especially in attached forms [ 6 , 22 , 25 , 26 , 33 ]. Therefore, in subsequent experiments we tested all antimicrobials for effectiveness in eliminating the attached biofilm form.…”
Section: Resultsmentioning
confidence: 99%
“…Based on findings from different techniques, we concluded that both whole bee venom and melittin could have significant effects on all Borrelia morphological forms including inhibiting the recovery of spirochetal cells and persisters as evidenced by recovery cultures in antimicrobial free media. Whole bee venom and melittin also significantly reduced the number and/or viability of attached biofilms, which based on previous research, is the most antibiotic resistant form of B. burgdorferi [ 6 , 25 , 26 ]. The MIC concentration values for melittin, for example, were in good agreement with previous studies that evaluated melittin on Borrelia spirochetes [ 29 ] and on several other gram-negative microorganisms such as S. enterica and Y. kristensenii [ 30 ].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations